You're Like Yourself : Multimodal Literacies in a Reading Support Class - Wissman, Kelly; Costello, Sean; Hamilton, Diane (Changing English, 2012)
This article explores the experiences and literacy practices of an adolescent boy enrolled in an academic support class, in which students received an open-ended invitation to respond to S.E. Hinton’s novel The Outsiders with the software programme Comic Life. In constructing this ‘telling case’, we highlight how traditional print literacies associated with English instruction can construct school as a ‘contradictory symbolic space’ for many students, but also how the introduction of the multimodalities can provide opportunities for adolescents to experience in-school literacies as social, performative and creative. We argue for re-envisioning literacy curricula and assessment not only to incorporate multimodalities, but also to provide students with instruction in writing conventions and practice with print in ways that serve larger purposes beyond remediation and test preparation. We posit the possibility for ‘complementary symbolic spaces’ that are connected to the landscape of adolescent literacies that students traverse outside school and to students’ desires to communicate, create and reach others within a range of discourse communities. Keywords: multimodalities; adolescent literacies; comics; narrative inquiry/
Keywords: adolescence; lecture numérique; multimodalité